Effect of primary tumor volume on survival of concurrent chemoradiotherapy in stage IV non‐small cell lung cancer - Xiaxia Chen; Wei Zhang; Lan Luo; Shimei Fu; Dongdong Cao; Shengfa Su; Qingsong Li; Wengang Yang; Yichao Geng; Bing Lu; Weiwei Ouyang (Cancer Medicine)
Abstract Objective To explore the survival effect of thoracic gross tumor volume (GTV) in three‐dimensional (3D) radiotherapy for stage IV non‐small cell lung cancer (NSCLC). Methods The data cases were obtained from a single‐center retrospective analysis. From May. From 2008 to August 2018, 377 treatment criteria were enrolled. GTV was defined as the volume of the primary lesion and the hilus as well as the mediastinal metastatic lymph node. Chemotherapy was a platinum‐based combined regimen of two drugs. The number of median chemotherapy cycles was 4 (2–6), and the cut‐off value of the planning target volume (PTV) dose of the primary tumor was 63 Gy (30–76.5 Gy). The cut‐off value of GTV volume was 150 cm3 (5.83–3535.20 cm3). Results The survival rate of patients with GTV <150 cm3 is better than patients with GTV ≥150 cm3. Multivariate Cox regression analyses suggested that peripheral lung cancer, radiation dose ≥63 Gy, GTV <150 cm3, 4–6 cycles of chemotherapy, and CR + PR are good prognostic factors for patients with stage IV non‐small cell lung cancer. The survival rate of patients with GTV <150 cm3 was longer than patients with ≥150 cm3 when they underwent 2 to 3 cycles of chemotherapy concurrent 3D radiotherapy (p < 0.05). When performing 4 to 6 cycles of chemotherapy concurrent 3D radiotherapy, there was no significant difference between <150 cm3 and ≥150 cm3. Conclusions The volume of stage IV NSCLC primary tumor can affect the survival of patients. Appropriate treatment methods can be opted by considering the volume of tumors to extend patients' lifetime to the utmost.